A New Paradigm of Primary Health Care in Kazakhstan: Personalized, Community-based, Standardized, and Technology-driven - Almaz Sharman (University Library System, University of Pittsburgh, 2014)
This paper discusses the need for change from Kazakhstan's current disease-centric healthcare paradigm to a new primary health and wellness-centric health care paradigm, technology-driven and based on personal relationships within a social context. While many different papers have been published about the importance of prevention and primary health care, few have focused on healthcare transition in Kazakhstan or other countries in Central Asia. The WHO's historic 1978 Alma-Ata Declaration signed in Kazakhstan promoted the centrality of primary care to the provision of effective, efficient, and equitable health services. Modern technologies such as the Internet, social media, and portable medical devices democratize medicine, providing great opportunities to rethink the Alma-Ata Declaration and reinvent primary health care on an entirely new platform that is knowledge-based and technology-assisted. The new paradigm suggested for the future development of health in Central Asian region emphasizes personal relationships and encourages sustainable solutions created by communities. This paper also introduces HealthCity, a new project in Kazakhstan aiming at introducing private, community-based and standardized primary healthcare that is driven by SmartHealth innovative technology.